Chronic vomiting in a case of citrullinaemia detected after treatment by total parenteral nutrition. Issue 5 (May 1984) - Benque, A; Bommelaer, G; Rozental, G; Cales, P; Cathelineau, L; Pham Dinh, D; Ribet, A
Abstract : We report a case of a 56 year old woman who presented with a long history of chronic attacks of vomiting. On admission to hospital she was cachectic, and attempted parenteral nutrition induced coma. The illness was found to be due to citrullinaemia, a metabolic disorder of the urea cycle. Our patient is the oldest with this disorder so far described in the literature. The main points of the case and its investigation are outlined: hyperammonaemia, amino acid chromatogram, measurement of enzyme activity in skin and liver biopsy material. The therapeutic measures which led to cure are of particular interest.